Exporting global jihad Volume One: Critical perspectives from Africa and Europe - Solomon, Hussein; Smith, Tom (London [England] I.B. Tauris & Co. Ltd, 2020)
About The Editors -- Contributor Bios -- Introduction: Examining The Global Linkages Of African And European Jihadists -- 'Glocalised' Jihad, Political Conflict, And Conspiracy Theorisation Across A Fragmented Somalia -- Global Or Local? Exploring The Emergence And Operation Of A Violent Islamist Network In Kenya -- Reflections On Islamist Militancy In The Sahel -- Jihad In Mali: Regional Conditions, Regional Goals, Global Importance -- Nigeria: The Rise And 'Fall' Of Boko Haram -- Libyan Jihadism: From Gadhafi And Tribalism To The Arab Spring And Tribalism -- Jihad And The United Kingdom -- Confronting Orientalism, Colonialism And Determinism: De-Constructing Contemporary French Jihadism -- Exporting Jihad From The Street-Level Groups In The Low Countries -- Scandinavian Jihad -- The Evolution Of The Jihad In Germany -- Al-Andalus: The Caliphate Of Cordoba Reimagined.
This timely 2 volume edited collection looks at the extent and nature of global jihad, focusing on the often-exoticised hinterlands of jihad beyond the traditionally viewed Middle Eastern 'centre'. As ISIS loses its footing in Syria and Iraq and al-Qaeda regroups this comprehensive account will be a key work in the on-going battle to better understand the dynamics of the jihads global reality. Critically examining the global reach of the jihad in these peripheries has the potential to tell us much about patterns of both local mobilisation, and local rejection of a grander centrally themed and administered jihad. Has the periphery been receptive to an exported jihad from the centre or does the local rooted cosmopolitanism of the jihad in the periphery suggest a more complex glocal relationship? These questions and challenges are more pertinent than ever as the likes of ISIS and many commentators, attempt to globally rebrand the jihad and as the centre reasserts its claims to the exotic periphery.Edited by Tom Smith (Portsmouth), Kirsten E. Schulze (LSE) and Hussein Solomon (UFS) the two volumes critically examine the various claims of connections between jihadist terrorism in the 'periphery', remote Islamist insurgencies of the 'periphery' and the global jihad. Each volume draws on experts in each of the geographies in question. The global nature of the jihad is too often taken for granted; yet the extent of the glocal connections deserve focused investigation. Without such inquiry we risk a reductive understanding of the global jihad, further fostering Orientalist and Eurocentric attitudes towards local conflicts and remote violence in the periphery
Also published in print.
Reproduktion
Mode of access: World Wide Web.
Barrierefreier Inhalt: Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Islam and world politics; Jihad; War -- Religious aspects -- Islam; Terrorismus; Internationaler Terrorismus; Dschihadismus; Militanz; Islam; Djihad; Religion & Politics; Erde; Afrika; Europa; Electronic books; Aufsatzsammlung; Fallstudiensammlung